2015
DOI: 10.2169/internalmedicine.54.3718
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Esomeprazole on Sleep in Patients with Gastroesophageal Reflux Disease as Assessed on Actigraphy

Abstract: Objective Gastroesophageal reflux disease (GERD) is strongly associated with sleep disturbances. Although treatment with proton pump inhibitors (PPIs) helps to improve GERD symptoms and subjective sleep parameters, the effects of PPI therapy on objective sleep parameters are conflicting. The aim of this study was to examine the effects of esomeprazole treatment on GERD symptoms and sleep parameters assessed using actigraphs and questionnaires. Methods Thirteen patients with GERD received 20 mg of esomeprazole … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 26 publications
0
3
0
Order By: Relevance
“…This study also reported that daily treatment with rabeprazole for 8 weeks decreased sleep disorders. However, Hiramoto et al ( 20 ) reported that once-daily treatment with esomeprazole for 2 weeks decreased GERD symptoms, but did not decrease sleep disorders. Whether the sleep disorders of partial responders can be improved by PPI therapy alone is a subject for future analysis.…”
Section: Discussionmentioning
confidence: 99%
“…This study also reported that daily treatment with rabeprazole for 8 weeks decreased sleep disorders. However, Hiramoto et al ( 20 ) reported that once-daily treatment with esomeprazole for 2 weeks decreased GERD symptoms, but did not decrease sleep disorders. Whether the sleep disorders of partial responders can be improved by PPI therapy alone is a subject for future analysis.…”
Section: Discussionmentioning
confidence: 99%
“…In a previous study, PPI treatment improved objective sleep parameters. Actigraphy, which is an ambulatory device, recorded motion in 13 GERD patients and showed that esomeprazole 20 mg increased the percentage of sleep time and decreased the wake time and sleep latency period; however, it failed to show progress in all objective sleep parameters …”
Section: Role Of Nocturnal Reflux Symptoms In Sleep Disordersmentioning
confidence: 99%
“…Actigraphy, which is an ambulatory device, recorded motion in 13 GERD patients and showed that esomeprazole 20 mg increased the percentage of sleep time and decreased the wake time and sleep latency period; however, it failed to show progress in all objective sleep parameters. 55 Several studies have investigated the association of GERD with nGER and sleep disturbances. PPI treatment has been shown to improve GERD-related sleep disturbances.…”
Section: Effect Of Reflux Treatment On Sleepmentioning
confidence: 99%